Architecture in Ancient Central Italy: connections in Etruscan and early Roman Building - Potts, CR (Cambridge University Press, 2022)
Architecture in Ancient Central Italy takes studies of individual elements and sites as a starting point to reconstruct a much larger picture of architecture in western central Italy as an industry, and to position the result in space (in the Mediterranean world and beyond) and time (from the second millennium BC to Late Antiquity). This volume demonstrates that buildings in pre-Roman Italy have close connections with Bronze Age and Roman architecture, with practices in local and distant societies, and with the natural world and the cosmos. It also argues that buildings serve as windows into the minds and lives of those who made and used them, revealing the concerns and character of communities in early Etruria, Rome, and Latium. Architecture consequently emerges as a valuable historical source, and moreover a part of life that shaped society as much as reflected it.